An alternative method of measuring the human maximal oxygen uptake (vO2Max) - Szubert, Józef; Szubert, Sławomir; Wieczorek, Wojciech; Szymańska-Paszczuk, Alicja; Ziółkowski, Włodzimierz; Szubert, Marietta (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
Introduction: One of the main tasks of the physiology of human exercise is the evaluation of physical efficiency. The maximal oxygen uptake (Vo2max) is the best indicator of physical fitness. It allows to widely predict a healthy organism’s response to physical strain. It is also considered useful in clinical research for evaluating patients’ ability to exercise, as well as monitoring the effects of their treatment or rehabilitation. Every method of measuring the maximal oxygen uptake has its limits and that is why a new, possibly simple, safe and reliable method of measuring Vo2max is constantly sought for. Materials and methods: On the basis of our own and worldwide empirical data, as well as the laws of thermodynamics and fluid mechanics, a new, accurate and safe method of measuring maximal oxygen uptake was developed. The method allows to evaluate Vo2max under various submaximal exercise loads. Results: There is no statistically significant difference between the maximal oxygen uptake values measured using the author’s method and those acquired using other researchers’ methods. Conclusion: The author’s method of measuring maximal oxygen uptake (Vo2max) can be a valid alternative to the currently used methods.